2015
DOI: 10.1039/c5nr03461b
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–solid spinodal decomposition mediated synthesis of Sb2Se3 nanowires and their photoelectric behavior

Abstract: The convenient synthesis of one-dimensional nanostructures of chalcogenide compounds with a visible band-gap is an essential research topic in developing next-generation photoelectronic devices. In particular, the design of a theoretically predictable synthesis process provides great flexibility and has a considerable ripple effect in nanotechnology. In this study, a novel rational growth approach is designed using the spinodal decomposition phenomenon for the synthesis of the Sb2Se3 nanowires, which is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Recently, as an alternative for well‐developed Cu(In,Ga)(S,Se) 2 and CdTe absorbers, Sb 2 (S 1‐x ,Se x ) 3 (0≤x≤1) (Sb 2 (S,Se) 3 ) has been explored widely duo to its characteristics of relative non‐toxicity and earth abundant components. What's more, Sb 2 (S,Se) 3 has suitable bandgap (1.03–1.8 eV), remarkable absorption coefficient (≈10 5 cm −1 ) and high mobility (≈42 cm 2 V · s −1 ) . The ns 2 lone pair state of Sb 2+ cation in Sb 2 (S,Se) 3 also unveils the development potential of Sb 2 (S,Se) 3 in photovoltaic application .…”
Section: Introductionmentioning
confidence: 87%
“…Recently, as an alternative for well‐developed Cu(In,Ga)(S,Se) 2 and CdTe absorbers, Sb 2 (S 1‐x ,Se x ) 3 (0≤x≤1) (Sb 2 (S,Se) 3 ) has been explored widely duo to its characteristics of relative non‐toxicity and earth abundant components. What's more, Sb 2 (S,Se) 3 has suitable bandgap (1.03–1.8 eV), remarkable absorption coefficient (≈10 5 cm −1 ) and high mobility (≈42 cm 2 V · s −1 ) . The ns 2 lone pair state of Sb 2+ cation in Sb 2 (S,Se) 3 also unveils the development potential of Sb 2 (S,Se) 3 in photovoltaic application .…”
Section: Introductionmentioning
confidence: 87%
“…For example, they showed that all the non‐oxide materials that were considered (III–V semiconductors, Si, SiC, Ge, and metal chalcogenides) would be ideal candidates for p‐type photocathodes because they are susceptible to oxidation but not to reduction. Moreover, predictions based on their computational approach have subsequently been validated by experimental measurements of photoelectrode reduction potentials …”
Section: Stability Against Photocorrosion Of Functionalized Photoelecmentioning
confidence: 80%
“…Therefore, most modeling approaches are yet to be extended to systematically understand and predict the effect of organic functional groups on photocorrosion resistance. This presents a significant gap between computational and more extensive experimental investigations of the stability of functionalized photoelectrodes.…”
Section: Stability Against Photocorrosion Of Functionalized Photoelecmentioning
confidence: 99%
“…Sb 2 Se 3 is also popularly known as a quasi‐1D (Q1D) material with an anisotropic orthorhombic structure, which can assist the transport of photoexcited carriers along the oriented (Sb 4 Se 6 ) n ribbons . Nanostructured Sb 2 Se 3 is reported to achieve a decent PEC hydrogen generation performance in the forms of nanoneedles, nanowires, and nanoarrays . These nanostructures could efficiently elevate the electrical and optical properties due to improved light absorption and charge carrier transportation .…”
Section: Introductionmentioning
confidence: 99%